Management and outcomes of breast cancer patients with radiotherapy interruption - Zhao, Fangrui; Yang, Dashuai; Lan, Yanfang; Li, Xiangpan (Frontiers in Oncology, 2024)
Background: Many cancer patients have not received timely treatment or even had treatment interruptions due to the COVID-19 pandemic. The objective of this investigation was to evaluate whether the prognosis of patients with breast cancer after surgery was affected by any interruptions in radiotherapy. Methods: The healthcare documents for breast cancer patients experiencing radiotherapy interruption after surgery, including treatment-related characteristics, as well as time of interruption, type of disease progression, and survival status, were collected between January and April 2020 during the Wuhan blockade. Results: The final number of patients included was 148, and neither the KM survival curve nor the cross-tabulation analysis found statistical significance. Cox regression analysis also did not identify risk factors associated with PFS.The prognosis of patients with postoperative breast cancer may not be significantly impacted by the interruption of radiotherapy, given its integration with additional treatments like targeted and endocrine therapies.